Phraseme beim DaF-Unterricht - Križaj, Lucija (Vestnik za tuje jezike, 2013)
I strongly believe that idioms which appear in everyday phrases should not be neglected when it comes to teaching a foreign language in schools. This article is a summary of my college diploma (with the same title: Teaching idioms in German as a foreign language lesson). The aim of my thesis was to draw up five different learning examples for comprehending idioms while teaching German as a foreign language.There are crucial differences in the process idioms are taught, far more complex than teaching material in the textbook; different preparation, knowledge, and skills are needed. Lesson plans are based on a textbook for High School education Studio d for the B1 level. Each individual lesson contains at least five (5) phrases that are directly or indirectly related to the theme in the textbook. The basis of every lesson plan consists from so-called phraseodidactic four-step:(1) searching for phrases in given text, (2) an understanding of phrases through text, images, or predictive associations, (3) consolidation through a variety of tasks, and (4) the use of idioms. In my opinion that is how, with sufficient knowledge and use of idioms, students also get to know and learn about the culture of the target language - which by itself culturally connects them closer to the language.
Keywords: frazemi; German; nemščina; tuji jeziki; phraseology; frazeologija; jezikovni pouk; didactic method; didaktika